Ti6Al4V lightweight lattice structures manufactured by laser powder bed fusion for load-bearing applications. (December 2018) - du Plessis, Anton; Yadroitsava, Ina; Yadroitsev, Igor
Highlights: Visualization of manufactured and compressed LPBF Ti6Al4V lattice structures using microCT scans. Structural mechanics simulation of lattice structures. Validation of simulations with physical compression tests. Both designs found experimentally to fail in the range 190–200 MPa. Mechanical properties of designed structures are close to the cortical bone. Abstract: Additively manufactured (AM) lattice structures allow complex-shaped and custom parts, with superior design that cannot be produced by traditional methods. For medical implants, AM lattice structures are aimed at matching the elastic modulus of bone while providing strength and allowing bone in-growth for long-term stability. In this study, relatively thick struts are investigated in an attempt to match the properties of cortical bone, which is meant for the internal structural integrity of the implant, while a smaller lattice may be used for near-surface parts of an implant. In this work we investigate additively manufactured lattice samples produced by Laser Powder Bed Fusion (LPBF) of Ti6Al4V ELI, with samples having approximately 50% regular porosity. In particular, we experimentally compare two designs: diagonal and rhombic. MicroCT-based static loading simulations are used to highlight stress hotspots in the two designs, to highlight possible failure locations. Physical compression testing to initial failure and subsequent microCT highlight the locations of initial failure, which correlate well with the simulation stress hotspots. Both designs show excellent strength (120–140 kN failure load) and effective compressive elastic modulus corresponding well to simulations. Differences between microCT-based simulations of the produced lattices and those of ideal design parameters can be attributed mainly to surface roughness, and slightly thinner manufactured struts of the as-built lattices, with similar trends for the two model designs. These results validate experimentally that both designs are suitable for load-bearing applications.